SEVERE TOXOCARA CATI INFECTION IN A DOMESTIC CAT: A CASE STUDY WITH PATHOLOGICAL AND HISTOPATHOLOGICAL FINDINGS IN SAYAN VILLAGE, UBUD - Dina Elviana; Nyoman Adi Suratma; I Ketut Berata; I Gusti Ketut Suarjana; Ida Bagus Kade Suardana (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Toxocariasis is a disease caused by worms of the genus Toxocara. In chronic cases, toxocariasis can lead to mortality due to damage to vital organs, including the lungs, liver, and intestines. The objective of this case study is a 2-month-old cat from Sayan Village, Ubud Subdistrict, Gianyar Regency, Bali, Indonesia. This case study aims to establish a diagnosis based on anamnesis, clinical signs, epidemiological data, anatomical pathology, histopathology, and laboratory examination results. Clinical symptoms observed in the case cat included emaciation, an enlarged abdomen, eye discharge, pale gums, rough fur, and liquid, foamy feces. Anatomical pathology examination revealed the presence of Toxocara cati worms, with a total count of 43 worms distributed throughout the small intestine, stomach, esophagus, trachea, and lungs. Fecal examination using qualitative methods detected Toxocara cati worm eggs. Histopathological observations indicated eosinophilic inflammatory cell infiltration in the small intestine and trachea. It was concluded that the case cat was diagnosed with toxocariasis. It was concluded that the cat was diagnosed with toxocariasis, which contributed to the severity of clinical symptoms and potentially mortality, emphasizing the need for effective preventive and biosecurity measures.